A method for preparing low thermal conductivity microporous refractory material

Through the secondary sintering of calcium powder, silicon fume and other materials and the use of polycarbosilane hydrogels, low thermal conductivity microporous refractory materials are formed, which solves the problem of thermal insulation requirements in high-temperature industrial environments and achieves low thermal conductivity and refractory materials. High mechanical strength improves the thermal efficiency and service life of the kiln lining.

CN118771868BActive Publication Date: 2025-01-10JIANGSU GREATWALL KILN & FURNACECT CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411267443.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-09-11
Publication Date
2025-01-10
Estimated Expiration
2044-09-11

AI Technical Summary

Technical Problem

The existing refractory materials cannot meet the insulation needs in high-temperature industrial environments. The traditional light-weight insulation materials have low strength, resulting in large heat capacity, reduced thermal efficiency, and increased pipe diameter.

Method used

The preparation method of low-thermal conduction microporous refractory materials is adopted to form microporous structures through secondary sintering of calcium powder, silicon fume and other materials, and polycarbosilane hydrogel and asphalt staple fiber are used during the sintering process, combined with ultrasonic stirring technology. A three-layer partition structure is formed to improve the mechanical strength and low thermal conductivity of the refractory material.

Benefits of technology

The low thermal conductivity and high mechanical strength of the refractory material are achieved, the thermal expansion rate is reduced, the problem of excessive porosity caused by primary sintering is avoided, and the insulation effect and service life of the kiln lining is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention discloses a method for preparing a low thermal conductivity microporous refractory material, and relates to the technical field of refractory materials. The invention uses calcium powder, silica fume and other materials as brick blanks of refractory materials, uses polycarbosilane hydrogel to bond two brick blanks, performs secondary sintering, and is assisted by aluminum vapor during the sintering process to form a strength gradient, which can greatly improve the mechanical strength of the refractory material, and the asphalt fiber in the gel has a low melting point and melts before the brick-making mud material at a lower temperature, thereby generating tiny holes in the gel, and the holes are affected by the gravity of the bricks above, so that the holes can penetrate the refractory materials above and below, forming a good fixing effect, and the hydrogel layer forms Si-Mg-C substances during the sintering process, which can effectively enhance the compression resistance of the refractory material and improve the low thermal conductivity of the refractory material. At the same time, the invention adopts a three-layer separation form, which is different from the traditional integral refractory material, and can effectively block heat transfer, thereby achieving low thermal conductivity.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of refractory materials, in particular to a method for preparing a low-thermal-conductivity microporous refractory material. Background Art

[0002] At present, although my country's thermal insulation materials are constantly improving and perfecting, they still cannot meet the increasingly demanding thermal insulation environment and requirements of high-temperature industries. In hot air and thermal pipelines, in order to ensure the temperature of high-temperature gases during transportation, refractory materials are built inside the pipelines. In the use of high-temperature kilns, in order to ensure the thermal insulation effect of the kiln and increase the service life of the kiln lining, a combination of heavy bricks and lightweight refractory materials is often used, resulting in a large thermal capacity of the kiln lining and reduced thermal efficiency. Due to the low strength of traditional lightweight insulation materials, they cannot be used directly in the working layer, and must be built with multiple layers of refractory materials, which increases the pipe diameter. Summary of the invention

[0003] The purpose of the present invention is to provide a method for preparing a low thermal conductivity microporous refractory material to solve the problems existing in the prior art.

[0004] In order to solve the above technical problems, the present invention provides the following technical solutions: a method for preparing a low thermal conductivity microporous refractory material, comprising the following preparation steps:

[0005] (1) Add 20-40 parts of calcium powder, 100-200 parts of silica fume, and 15-44 parts of feldspar into a grinder, grind at 600-800 rpm for 8-16 minutes, add 0.05 times the total weight of the powder into water, continue grinding for 10-15 minutes, then add 7-15 parts of lime milk and 8-20 parts of bentonite, continue grinding for 1-2 minutes, and obtain brick mud;

[0006] (2) Pour the brick mud into the mold and press it on a brick press at a pressure of 50T to make a soft brick blank;

[0007] (3) At an ultrasonic power of 50-80 W, an ultrasonic frequency of 20-25 kHz, and a speed of 60-80 rpm, mix the thermoplastic phenolic resin, alcohol solvent, and curing agent in a mass ratio of 1:8-11:0.02-0.05. After ultrasonic stirring for 5-10 min, adjust the stirring speed to 200-300 rpm and the ultrasonic power to 250-300 W. Add 0.1-0.2 times the total mass of the solution of asphalt short fibers with a length of 6-12 mm, The total mass of the solution is 0.01-0.04 times the magnesium oxide with a particle size of 20-70 nm. After ultrasonic stirring for 15-20 minutes, a polycarbosilane / cyclohexane solution with a mass concentration of 6-10% is added according to the mass ratio of thermoplastic phenolic resin to polycarbosilane of 1:1, the rotation speed is adjusted to 600-800 rpm, and after stirring for 10-20 minutes, the stirring and ultrasonication are stopped, and the mixture is reacted at 80-150° C. for 8-10 hours, and then placed at 80° C. for 24 hours to obtain a wet gel;

[0008] (4) The soft brick, wet gel and soft brick are stacked in order, dried at 60-150°C for 24 hours, and then heated to 1450-1500°C at 3°C / min under argon protection, and aluminum vapor is introduced at 20-50 L / h. After keeping warm for 1-2 hours, the aluminum vapor is stopped, and the temperature is raised to 1600-1650°C at 3°C / min, and kept warm for 3 hours. After naturally cooling to room temperature, the temperature is raised to 1000-1200°C at 10°C / min, and kept warm for 30 minutes. Then, the temperature is lowered to 40°C at 2°C / min to obtain a low thermal conductivity microporous refractory material.

[0009] Furthermore, the lime milk in step (1) is made of lime having a calcium oxide content of 70%.

[0010] Furthermore, the asphalt short fibers in step (3) are prepared by melt spinning of asphalt having an intermediate phase content of 100% and a softening point of 240-280°C.

[0011] Furthermore, the mass ratio of anhydrous ethanol to n-propanol in the alcohol solvent in step (3) is 1-4:1-2.

[0012] Furthermore, the mass ratio of p-toluenesulfonic acid to diethyl sulfate in the curing agent of step (3) is 2-5:0.1-2.

[0013] Furthermore, in step (4), the thickness ratio of the soft brick, wet gel and soft brick is 10:1:10.

[0014] Compared with the prior art, the beneficial effects achieved by the present invention are:

[0015] (1) Add calcium powder, silica fume and other materials as the main raw materials of refractory materials and carry out secondary sintering. During the first sintering process, calcium powder decomposes at high temperature to form calcium oxide and carbon dioxide gas. The gas escapes to form a microporous structure, which reduces the thermal conductivity of the refractory materials. At the same time, the first sintering is assisted by aluminum vapor. Aluminum vapor combines with calcium oxide and SiO2 to form crystals. Due to the diffusion effect of vapor, a bonding strength gradient is formed inside the refractory materials, which can greatly improve the mechanical strength and refractoriness of the refractory materials. After cooling, the second sintering is carried out. The secondary sintering is conducive to crystal growth, full sintering, and adjustment of the porosity of the refractory materials, avoiding the primary sintering. The refractory porosity is too high and affects its performance;

[0016] (2) The present invention compacts materials such as calcium powder and silica fume under a certain pressure to make the materials soft, and then uses polycarbosilane hydrogel as an adhesive between the two blocks. The polycarbosilane hydrogel uses phenolic resin as a base material, mixed with polycarbosilane, asphalt chopped fibers and magnesium oxide. The hydrogel is assisted by ultrasonic stirring during the preparation process to make the asphalt fibers evenly dispersed in the hydrogel system, and then undergoes secondary sintering. During the sintering process, the asphalt fibers in the hydrogel have a low melting point and melt at a lower temperature before the brick mud, thereby producing fine pores in the gel, which are affected by the bricks above. Due to the gravity, the holes can penetrate the upper and lower refractory materials to form a good fixing effect, and the hydrogel layer forms Si-Mg-C material during the sintering process, which can effectively enhance the compression resistance of the refractory material and reduce the thermal expansion rate of the refractory material. At the same time, the Si-Mg-C material in the middle layer has a lower thermal conductivity coefficient, which can improve the low thermal conductivity of the refractory material. At the same time, the present invention adopts a three-layer separation form of refractory material-gel-refractory material, which is different from the traditional integral refractory material and can effectively block heat transfer, thereby achieving low thermal conductivity. DETAILED DESCRIPTION

[0017] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0018] In order to more clearly illustrate the method provided by the present invention, the following examples are used to describe in detail the test methods of various indicators of the refractory materials prepared in the following examples:

[0019] Compressive strength: refer to GB / T3997.2

[0020] Thermal conductivity: Refer to YB / T4130

[0021] Example 1; (1) 20 parts of calcium powder, 100 parts of silica fume and 15 parts of feldspar were added to a grinder, and ground at 600 rpm for 8 minutes, and 0.05 times the total weight of the powder was added with water, and the grinding was continued for 10 minutes, and then 7 parts of lime milk and 8 parts of bentonite were added, and the grinding was continued for 1 minute to obtain brick mud; the lime milk was made of lime with a calcium oxide content of 70%;

[0022] (2) Pour the brick mud into the mold and press it on a brick press under a pressure of 50T to make a soft brick blank;

[0023] (3) Under the conditions of ultrasonic power of 50-80 W, ultrasonic frequency of 20 kHz and 60 rpm, thermoplastic phenolic resin, alcohol solvent and curing agent were mixed in a mass ratio of 1:8:0.02. After ultrasonic stirring for 5 min, the stirring speed was adjusted to 200 rpm and the ultrasonic power was adjusted to 250 W. 0.1 times the total mass of the solution of asphalt short fibers with a length of 6 mm and 0.01 times the total mass of the solution of magnesium oxide with a particle size of 20 nm were added. After ultrasonic stirring for 15 min, the thermoplastic phenolic resin and polycarbonate were mixed. The mass ratio of silane is 1:1, and the mass concentration of 6% polycarbosilane / cyclohexane solution is added, and the rotation speed is adjusted to 600 rpm. After stirring for 10 minutes, stirring and ultrasonication are stopped, and the mixture is reacted at 80°C for 8 hours, and then placed at 80°C for 24 hours to obtain a wet gel; the asphalt short fiber is prepared by melt spinning of asphalt with an intermediate phase content of 100% and a softening point of 240°C; the mass ratio of anhydrous ethanol and n-propanol in the alcohol solvent is 1:1; the mass ratio of p-toluenesulfonic acid and diethyl sulfate in the curing agent is 2:0.1;

[0024] (4) The soft brick, wet gel and soft brick were stacked in order with a thickness ratio of 10:1:10. After drying at 60°C for 24 hours, the temperature was raised to 1450°C at 3°C / min under argon protection, and aluminum vapor was introduced at 20 L / h. After keeping warm for 1 hour, the aluminum vapor was stopped, the temperature was raised to 1600°C at 3°C / min, kept warm for 3 hours, and naturally cooled to room temperature. The temperature was then raised to 1000°C at 10°C / min, kept warm for 30 minutes, and then cooled to 40°C at 2°C / min to obtain a low thermal conductivity microporous refractory material.

[0025] Example 2; (1) 30 parts of calcium powder, 150 parts of silica fume and 32 parts of feldspar were added to a grinder, ground at 700 rpm for 12 minutes, 0.05 times the total mass of the powder was added with water, and the grinding was continued for 12 minutes, and then 11 parts of lime milk and 14 parts of bentonite were added, and the grinding was continued for 2 minutes to obtain brick mud; the lime milk was made of lime with a calcium oxide content of 70%;

[0026] (2) Pour the brick mud into the mold and press it on a brick press under a pressure of 50T to make a soft brick blank;

[0027] (3) Under the conditions of ultrasonic power of 60 W, ultrasonic frequency of 22 kHz and 70 rpm, thermoplastic phenolic resin, alcohol solvent and curing agent were mixed in a mass ratio of 1:10:0.04. After ultrasonic stirring for 7 min, the stirring speed was adjusted to 250 rpm and the ultrasonic power was adjusted to 280 W. 0.15 times the total mass of the solution of asphalt short fibers with a length of 9 mm and 0.03 times the total mass of the solution of magnesium oxide with a particle size of 45 nm were added. After ultrasonic stirring for 18 min, the thermoplastic phenolic resin and polycarbosilane were mixed in a mass ratio of 1:10:0.04. After ultrasonic stirring for 7 min, the stirring speed was adjusted to 250 rpm and the ultrasonic power was adjusted to 280 W. Add a polycarbosilane / cyclohexane solution with a mass concentration of 8% in a mass ratio of 1:1, adjust the speed to 700rpm, stir for 15 minutes, stop stirring and ultrasonication, react at 110°C for 9 hours, and then place at 80°C for 24 hours to obtain a wet gel; the asphalt short fiber is prepared by melt spinning of asphalt with an intermediate phase content of 100% and a softening point of 245°C; the mass ratio of anhydrous ethanol and n-propanol in the alcohol solvent is 2:1.5; the mass ratio of p-toluenesulfonic acid and diethyl sulfate in the curing agent is 3:1;

[0028] (4) The soft brick, wet gel and soft brick were stacked in order with a thickness ratio of 10:1:10. After drying at 115°C for 24 hours, the temperature was raised to 1455°C at 3°C / min under argon protection, and aluminum vapor was introduced at 35 L / h. After keeping warm for 1.5 hours, the aluminum vapor was stopped, the temperature was raised to 1625°C at 3°C / min, and kept warm for 3 hours. After naturally cooling to room temperature, the temperature was raised to 1100°C at 10°C / min, and kept warm for 30 minutes. Then the temperature was lowered to 40°C at 2°C / min to obtain a low thermal conductivity microporous refractory material.

[0029] Example 3; (1) 40 parts of calcium powder, 200 parts of silica fume and 44 parts of feldspar were added to a grinder, ground at 800 rpm for 16 minutes, 0.05 times the total weight of the powder was added with water, and the grinding was continued for 15 minutes, and then 15 parts of lime milk and 20 parts of bentonite were added, and the grinding was continued for 2 minutes to obtain brick mud; the lime milk was made of lime with a calcium oxide content of 70%;

[0030] (2) Pour the brick mud into the mold and press it on a brick press under a pressure of 50T to make a soft brick blank;

[0031] (3) Under the conditions of ultrasonic power of 80 W, ultrasonic frequency of 25 kHz and 80 rpm, thermoplastic phenolic resin, alcohol solvent and curing agent were mixed in a mass ratio of 1:11:0.05. After ultrasonic stirring for 10 min, the stirring speed was adjusted to 300 rpm and the ultrasonic power was adjusted to 300 W. Asphalt short fibers with a length of 12 mm and a particle size of 70 nm, which were 0.2 times the total mass of the solution, and magnesium oxide with a particle size of 70 nm, which were 0.04 times the total mass of the solution, were added. After ultrasonic stirring for 20 min, the thermoplastic phenolic resin and polycarbosilane were mixed. A polycarbosilane / cyclohexane solution with a mass ratio of 1:1 is added, the rotation speed is adjusted to 800 rpm, and after stirring for 20 minutes, stirring and ultrasonication are stopped, and the mixture is reacted at 150°C for 10 hours, and then placed at 80°C for 24 hours to obtain a wet gel; the asphalt short fiber is prepared by melt spinning of asphalt with a mesophase content of 100% and a softening point of 245°C; the mass ratio of anhydrous ethanol to n-propanol in the alcohol solvent is 4:2; the mass ratio of p-toluenesulfonic acid to diethyl sulfate in the curing agent is 5:2;

[0032] (4) The soft bricks, wet gel and soft bricks are stacked in order with a thickness ratio of 10:1:10. After drying at 150°C for 24 hours, the temperature is raised to 1500°C under argon protection, and aluminum vapor is introduced at a rate of 50 L / h. After keeping the temperature for 2 hours, the aluminum vapor is stopped and the temperature is raised to 1650°C at a rate of 3°C / min and kept at this temperature for 3 hours. After naturally cooling to room temperature, the temperature is raised to 1200°C at a rate of 10°C / min and kept at this temperature for 30 minutes. Then the temperature is lowered to 40°C at a rate of 2°C / min to obtain a low thermal conductivity microporous refractory material.

[0033] Comparative Example 1: The difference between Comparative Example 1 and Example 2 is that step (1) is different. Step (1) is changed to: add 150 parts of silica fume and 32 parts of feldspar into a grinder, grind at 700 rpm for 12 minutes, add 0.05 times the total mass of the powder of water, continue grinding for 12 minutes, then add 11 parts of lime milk and 14 parts of bentonite, continue grinding for 2 minutes, and obtain brick mud; the lime milk is made of lime with a calcium oxide content of 70%; the remaining steps are the same as Example 2.

[0034] Comparative Example 2: The difference between Comparative Example 2 and Example 2 is that step (4) is different. Step (4) is changed to: stack the soft brick, wet gel and soft brick in sequence with a thickness ratio of 10:1:10, dry at 115°C for 24 hours, and then heat to 1625°C at 3°C / min under argon protection, keep warm for 3 hours, and then naturally cool to room temperature, and then heat to 1100°C at 10°C / min, keep warm for 30 minutes, and then cool to 40°C at 2°C / min to obtain a low thermal conductivity microporous refractory material; the remaining steps are the same as Example 2.

[0035] Comparative Example 3: The difference between Comparative Example 3 and Example 2 is that step (4) is different. Step (4) is changed to: stack the soft brick blank, wet gel and soft brick blank in sequence with a thickness ratio of 10:1:10, dry at 115°C for 24 hours, and then heat to 1455°C at 3°C / min under argon protection. Aluminum vapor is introduced at 35L / h. After keeping warm for 1.5 hours, the aluminum vapor is stopped, and the temperature is raised to 1625°C at 3°C / min. Keep warm for 3 hours, and then naturally cool to room temperature to obtain a low thermal conductivity microporous refractory material. The remaining steps are the same as Example 2.

[0036] Comparative Example 4: The difference between Comparative Example 4 and Example 2 is that step (3) is different. Step (3) is changed to: under an ultrasonic power of 60 W, an ultrasonic frequency of 22 kHz, and 70 rpm, the thermoplastic phenolic resin, the alcohol solvent, and the curing agent are mixed in a mass ratio of 1:10:0.04, and ultrasonic stirring is performed for 7 min. Then, the stirring speed is adjusted to 250 rpm and the ultrasonic power is adjusted to 280 W. Magnesium oxide having a particle size of 45 nm and a mass of 0.03 times the total mass of the solution is added. After ultrasonic stirring for 18 min, the thermoplastic phenolic resin and the polycarbosilane are mixed in a mass ratio of 1:10:0.04. A polycarbosilane / cyclohexane solution with a mass concentration of 8% is added in a mass ratio of 1:1, the rotation speed is adjusted to 700 rpm, and after stirring for 15 minutes, stirring and ultrasound are stopped, the mixture is reacted at 110°C for 9 hours, and then placed at 80°C for 24 hours to obtain a wet gel; the asphalt short fiber is prepared by melt spinning of asphalt with an intermediate phase content of 100% and a softening point of 245°C; the mass ratio of anhydrous ethanol and n-propanol in the alcohol solvent is 2:1.5; the mass ratio of p-toluenesulfonic acid and diethyl sulfate in the curing agent is 3:1; the remaining steps are the same as in Example 2.

[0037] Comparative Example 5: The difference between Comparative Example 5 and Example 2 is that step (3) is different. Step (3) is changed to: under an ultrasonic power of 60 W, an ultrasonic frequency of 22 kHz, and 70 rpm, the thermoplastic phenolic resin, the alcohol solvent, and the curing agent are mixed in a mass ratio of 1:10:0.04. After ultrasonic stirring for 7 minutes, the stirring speed is adjusted to 250 rpm and the ultrasonic power is adjusted to 280 W. 0.15 times the total mass of the solution and the length of 9 mm asphalt short fibers are added. After ultrasonic stirring for 18 minutes, the thermoplastic phenolic resin and polycarbosilane are mixed. A polycarbosilane / cyclohexane solution with a mass ratio of 1:1 is added, the rotation speed is adjusted to 700 rpm, and after stirring for 15 minutes, stirring and ultrasound are stopped, the mixture is reacted at 110°C for 9 hours, and then placed at 80°C for 24 hours to obtain a wet gel; the asphalt short fiber is prepared by melt spinning of asphalt with an intermediate phase content of 100% and a softening point of 245°C; the mass ratio of anhydrous ethanol and n-propanol in the alcohol solvent is 2:1.5; the mass ratio of p-toluenesulfonic acid and diethyl sulfate in the curing agent is 3:1; and the remaining steps are the same as in Example 2.

[0038] Comparative Example 6

[0039] (1) Add 30 parts of calcium powder, 150 parts of silica fume, and 32 parts of feldspar into a grinder, grind at 700 rpm for 12 minutes, add 0.05 times the total weight of the powder into water, continue grinding for 12 minutes, then add 11 parts of lime milk and 14 parts of bentonite, continue grinding for 2 minutes, and obtain brick mud; the lime milk is made of lime with a calcium oxide content of 70%;

[0040] (2) Pour the brick mud into a mold, press it into shape on a brick press at a pressure of 500T, and under argon protection, heat it to 1455℃ at 3℃ / min, introduce aluminum vapor at 35L / h, keep it warm for 1.5h, stop introducing aluminum vapor, heat it to 1625℃ at 3℃ / min, keep it warm for 3h, cool it naturally to room temperature, heat it to 1100℃ at 10℃ / min, keep it warm for 30min, and then cool it to 40℃ at 2℃ / min to obtain a low thermal conductivity microporous refractory material.

[0041] Effect example

[0042] Table 1 below shows the performance analysis results of the refractory materials of Examples 1 to 3 of the present invention and Comparative Examples 1 to 6.

[0043] Table 1

[0044] The present invention uses calcium powder, silica fume and other materials as the main raw materials of refractory materials, performs secondary sintering, and assists with aluminum vapor during the sintering process to form a strength gradient, which can greatly improve the mechanical strength of the refractory materials, and the secondary sintering is beneficial to the growth of crystals, thereby improving the strength of the refractory materials; the present invention compacts calcium powder, silica fume and other materials under a certain pressure to make the materials soft, and then uses polycarbosilane hydrogel as an adhesive between two pieces. The polycarbosilane hydrogel uses phenolic resin as a base material, and is mixed with polycarbosilane, asphalt chopped fibers and magnesium oxide. The hydrogel is assisted by ultrasonic stirring during the preparation process, so that the asphalt short fibers are evenly dispersed in the hydrogel system, and then performs secondary sintering. During the sintering process, the water The asphalt short fibers in the gel have a low melting point and melt before the brick-making mud at a lower temperature, thereby producing tiny holes in the gel. Under the gravity of the bricks above, the holes can penetrate the upper and lower refractory materials, forming a good fixing effect. The hydrogel layer forms Si-Mg-C material during the sintering process, which can effectively enhance the compression resistance of the refractory material and reduce the thermal expansion rate of the refractory material. At the same time, the Si-Mg-C material in the middle layer has a lower thermal conductivity coefficient, which can improve the low thermal conductivity of the refractory material. At the same time, the present invention adopts a three-layer separation form of refractory material-gel-refractory material, which is different from the traditional integral refractory material and can effectively block heat transfer, thereby achieving low thermal conductivity.

[0045] It will be apparent to those skilled in the art that the invention is not limited to the details of the exemplary embodiments described above and that the invention can be implemented in other specific forms without departing from the spirit or essential features of the invention. Therefore, the embodiments should be considered in all respects as exemplary and non-limiting, and the scope of the invention is defined by the appended claims rather than the foregoing description, and it is intended that all variations within the meaning and scope of the equivalent elements of the claims be included in the invention. Any marking in a claim should not be considered as limiting the claim to which it relates.

Claims

1. A method for preparing a low thermal conductivity microporous refractory material, characterized in that: The method comprises the following preparation steps: (1) Add 20-40 parts of calcium powder, 100-200 parts of silica fume, and 15-44 parts of feldspar into a grinder, grind at 600-800 rpm for 8-16 minutes, add 0.05 times the total weight of the powder into water, continue grinding for 10-15 minutes, then add 7-15 parts of lime milk and 8-20 parts of bentonite, continue grinding for 1-2 minutes to obtain brick mud. The calcium powder decomposes at high temperature to form calcium oxide and carbon dioxide gas, and the gas escapes to form a microporous structure. (2) Pour the brick mud into the mold and press it on a brick press at a pressure of 50T to make a soft brick blank; (3) At an ultrasonic power of 50-80 W, an ultrasonic frequency of 20-25 kHz, and a speed of 60-80 rpm, mix the thermoplastic phenolic resin, alcohol solvent, and curing agent in a mass ratio of 1:8-11:0.02-0.

05. After ultrasonic stirring for 5-10 min, adjust the stirring speed to 200-300 rpm and the ultrasonic power to 250-300 W. Add 0.1-0.2 times the total mass of the solution of asphalt short fibers with a length of 6-12 mm, The total mass of the solution is 0.01-0.04 times the magnesium oxide with a particle size of 20-70 nm. After ultrasonic stirring for 15-20 minutes, a polycarbosilane / cyclohexane solution with a mass concentration of 6-10% is added according to the mass ratio of thermoplastic phenolic resin to polycarbosilane of 1:1, the rotation speed is adjusted to 600-800 rpm, and after stirring for 10-20 minutes, the stirring and ultrasonication are stopped, and the mixture is reacted at 80-150° C. for 8-10 hours, and then placed at 80° C. for 24 hours to obtain a wet gel; (4) The soft bricks, wet gel and soft bricks are stacked in order, dried at 60-150°C for 24 hours, and then heated to 1450-1500°C at 3°C / min under argon protection, and aluminum vapor is introduced at 20-50 L / h. After keeping warm for 1-2 hours, the introduction of aluminum vapor is stopped, and the temperature is raised to 1600-1650°C at 3°C / min, and kept warm for 3 hours. After naturally cooling to room temperature, the temperature is raised to 1000-1200°C at 10°C / min, and kept warm for 30 minutes. Then, the temperature is lowered to 40°C at 2°C / min to obtain a low thermal conductivity microporous refractory material.

2. The method for preparing a low thermal conductivity microporous refractory material according to claim 1, characterized in that: The lime milk in step (1) is made of lime with a calcium oxide content of 70%.

3. The method for preparing a low thermal conductivity microporous refractory material according to claim 1, characterized in that: The asphalt short fibers in step (3) are prepared by melt spinning of asphalt having a mesophase content of 100% and a softening point of 240-280°C.

4. The method for preparing a low thermal conductivity microporous refractory material according to claim 1, characterized in that: The mass ratio of anhydrous ethanol to n-propanol in the alcohol solvent of step (3) is 1-4:1-2.

5. The method for preparing a low thermal conductivity microporous refractory material according to claim 1, characterized in that: The mass ratio of p-toluenesulfonic acid to diethyl sulfate in the curing agent of step (3) is 2-5:0.1-2.

6. The method for preparing a low thermal conductivity microporous refractory material according to claim 1, characterized in that: In step (4), the thickness ratio of the soft brick blank, wet gel and soft brick is 10:1:

10.

7. The method for preparing a low thermal conductivity microporous refractory material according to claim 1, characterized in that: The low thermal conductivity microporous refractory material has a total porosity of 72-77% and a closed porosity of 41.7-43%.

Citation Information

Patent Citations

  • ZTA ceramic material preparation method and material prepared from method

    CN110015889A

  • High-temperature-resistant anti-radiation interlayer thermal protection material and preparation method thereof

    CN113603470A